(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
implementing of distribution and transmission power systems for urban areas and for future renewable energy to meet future demand is a challenging task when conventional cables and transformers are considered. Therefore, there are several methods, that have applied in conational power systems to reduce power losses, voltage regulator issues , capital cost of whole system and increasing power delivering in urban areas and from offshore farms ,such as carefully sited and operated distributed generation (DG) and distributed control techniques. However, these techniques may raise others challenges in networks such as stability, voltage regulators issues and increasing capital cost of networks. Since High Temperature Superconductor (HTS) cables exhibit zero resistance when cooled to the boiling point of liquid nitrogen (77Keliven), they have the potential to be used to address these issues in distribution and transmission networks. Consequently, this paper reviews super-conductor power systems: the work previously achieved in the DC and AC superconductor power systems and describes the materials and methods which they used. In addition, it shows how the superconductor technologies can address these issues when they are used for distribution and transmission powe r systems.